Climate Change Impacts on Coffee Production in Mexico and Central America - Bunn, Christian; Lundy, Mark M.; Castro-Llanos, Fabio Alexander (International Center for Tropical Agriculture, 2019)
This atlas for Central America provides general information on the different degrees of adaptation efforts needed to mitigate climate change impacts on coffee production, as well as maps of the region and of each country, agroclimatic zone maps (ACZ), and impact gradient maps. This information facilitates having a better outlook of the region regarding the effects of climate change on coffee in the region and opens the debate on sustainable practices and necessary investments to face future risks. The map of coffee presences helps identify coffee production zones; maps of agroclimatic zones show future changes of agroclimatic zones suitable to grow coffee; the maps of impact gradient help identify the level of impact in each zone, first on the region, but also by country. All the maps in this Atlas, as well as the data from which they were created can be downloaded and reused.